Pengembangan Sistem Temu Kembali Informasi untuk Pencarian Sarana Kesehatan Diwilayah Solo - Sariningrum, Pradani; , Hernawan Sulistyanto, S.T., M.T (2016)
Abstract Society needed health care to support survival . Number of health providers in the region that is now widely spread confusion solo lead people to choose the right service . One of the applications needed to handle this problem is finding health facilities by the method of retrieval system known as information retrieval system . Thus society even laymen can easily use . In this study , we tried to simplify the search for information by using web-based information retrieval by indexing documents using keywords (query ) . Queries are stored to be processed to display the corresponding information . This study will help public health facilities in the region seek to Solo more precisely match the expected service.